Broad-host-range lytic Erwinia phage Key with exopolysaccharide degrading activity - Zlatohurska, Maryna; Gorb, Tetiana; Romaniuk, Liudmyla; Shenderovska, Natalia; Faidiuk, Yuliia; Zhuminska, Ganna; Hubar, Yuliia; Hubar, Oleksandr; Kropinski, Andrew M.; Kushkina, Alla; Tovkach, Fedor (Virus research, 2023)
•The broad-host-range lytic phage Key is the first isolated and sequenced T5-related phage shown to infect pathogenic species of Erwiniaceae.•Based on the revealed genome synteny and the results of phylogenetic analysis, phage Key, together with its closest relative, Pantoea phage AAS21, form a novel genus within the Demerecviridae family.•The gene of an exopolysaccharide depolymerase similar to many Erwinia-specific phages was found in the genome of phage Key. In this study, the genome of the lytic broad-host-range phage Key infecting Erwinia amylovora, Erwinia horticola, and Pantoea agglomerans strains was characterized. Key phage has a 115,651 bp long double-stranded DNA genome with the G + C ratio of 39.03%, encoding 182 proteins and 27 tRNA genes. The majority (69%) of predicted coding sequences (CDSs) encode proteins with unknown functions. The protein products of 57 annotated genes were found to have probable functions in nucleotide metabolism, DNA replication, recombination, repair, and packaging, virion morphogenesis, phage-host interaction and lysis. Furthermore, the product of gene 141 shared amino acid sequence similarity and conserved domain architecture with the exopolysaccharide (EPS) degrading proteins of Erwinia and Pantoea infecting phages as well as bacterial EPS biosynthesis proteins. Due to the genome synteny and similarity to the proteins of T5-related phages, phage Key, together with its closest relative, Pantoea phage AAS21, was suggested to represent a novel genus within the Demerecviridae family, for which we tentatively propose the name “Keyvirus”.